Radiation Dose to the Skin and to the Gonads from Diagnostic X-Ray Procedures - Duggan, H. E. (1963)
The design of a study to assess the hazard to patients from radiation received during diagnostic radiological procedures is described. The long-term accumulation of data relating to the skin and gonadal doses received by patients in a large x-ray department has been initiated. This will serve as a model for any situation involving small recurrent radiation doses to a significant proportion of the population. A description is given of the basic dose measurements made and the method used in calculating and recording the skin and gonadal doses for each patient. Although no definite conclusions concerning the presence or absence of a radiation hazard have yet been made, the proposed future course of this study is discussed.